How Young Adolescents Draw Themselves: A Comparison Across Three Ecosocial Contexts in Southern Madagascar. (February 2019) - Scheidecker, Gabriel; Gernhardt, Ariane; Rübeling, Hartmut; Holtmannspötter, Jona; Keller, Heidi
The present study investigated the impact of young adolescents' learning environment on their culturally mediated view of themselves as expressed in their self-drawings. The sample consisted of 83 young adolescents, 35 male and 48 female, aged 10 to 14 years with an overall average of 12 years living in three diverse ecosocial contexts within the Southern region of Madagascar: 28 participants were recruited in rural villages, 14 adolescents lived in a small town, and 41 adolescents were raised in a large city. The participants did not differ in age or gender distribution. The analyses revealed significant differences in the adolescents' emotional expressions, drawing styles, visual appearances, and figure sizes in their self-depictions, which were in line with ecosocial variations in their learning environments. The findings are interpreted in light of the participants' varying socialization experiences, access to formal education, and exposure to modern media and a Western lifestyle.